2021
DOI: 10.3390/ani11082279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Algae-Derived Polysaccharides on Morphology, Tight Junctions, Antioxidant Capacity and Immune Response of Duodenum in Broilers under Heat Stress

Abstract: To evaluate the ameliorative effect of algae-derived polysaccharide (ADP) supplementation on duodenal injury caused by heat stress (HS) in broilers, a total of 144 male yellow-feathered broilers (56-day-old) were randomly allocated into three groups: The TN group (thermoneutral zone, broilers were raised at 23.6 ± 1.8 °C); HS group (heat stress, broilers were exposed to 33.2 ± 1.5 °C 10 h/day, 8:00 a.m.–18:00 p.m., the temperature in the remaining period was consistent with the TN group); HSA group (heat-stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 57 publications
3
41
0
2
Order By: Relevance
“…E. prolifera polysaccharides (EP) are made up of α- and β-( 1 , 4 )- linked monosaccharides (rhamnose, xylose, and glucuronic acid) ( 13 ), where the sulfate group is attached at the C-3 position of rhamnose ( 14 ). Recent studies indicated increased production performance, breast muscle yield, egg quality, antioxidant capacity, and intestinal morphology of chickens fed seaweed polysaccharides ( 15 18 ). In addition, EP supplementation increased the weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…E. prolifera polysaccharides (EP) are made up of α- and β-( 1 , 4 )- linked monosaccharides (rhamnose, xylose, and glucuronic acid) ( 13 ), where the sulfate group is attached at the C-3 position of rhamnose ( 14 ). Recent studies indicated increased production performance, breast muscle yield, egg quality, antioxidant capacity, and intestinal morphology of chickens fed seaweed polysaccharides ( 15 18 ). In addition, EP supplementation increased the weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macroalgae-enriched feed has proven useful for ameliorating intestinal architecture in broiler chickens [ 15 , 16 ]. However, the influence of microalgae administration on intestinal health has not been documented extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, extracts from various plants have proved useful for such purposes [ 12 , 13 , 14 ]. Algae administration has also yielded positive outcomes with regard to animal performance and immunity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the application of antibiotics for growth promotion in farm animals was banned entirely in the European Union since 2000 and in South Korea and Japan after 2011 (41). Recently, China also completely banned the preventive antibiotics for promoting the growth performance of animals to mitigate the deleterious consequences of AMR to public health and encouraged research on alternatives to preventive antibiotics (42)(43)(44)(45). Nevertheless, in large-scale aquaculture, the extensive use of therapeutic antibacterial drugs induced the AMR issues and was still a major concern.…”
Section: Discussionmentioning
confidence: 99%